Isolated pulmonary amyloidoma: A rare cause of solitary pulmonary nodule. (2023) - DeCicco, Danielle; Alshaikhnassir, Esra; Deepak, Vishal; Hadique, Sarah; Sangani, Rahul
Abstract: Pulmonary nodules are a frequent finding on imaging, especially given screening guidelines for lung cancer with low dose computed tomography (CT) scan. Here, we report a case with a single pulmonary nodule in a patient exposed to coal dust and asbestos. The nodule had benign features, but it showed an increase in size on repeated imaging. A CT-guided biopsy followed by mass spectrometry of the sample identified the nodule as the AL subtype of amyloidoma. A bone marrow biopsy was without evidence for malignancy including lymphoma. Nodular pulmonary amyloidosis (NPA) is rare, and a biopsy is required to establish the diagnosis. NPA generally does not affect lung function or impact survival; thus NPA does not require specific therapy. This case is the first documented case associated with coal-dust exposure. High-risk patients need to be followed longitudinally due to association of amyloidosis with lymphoma and other systemic conditions.